Specificity of Psychological Structure of Responsibility as Professionally Important Personality Trait in Military Personnel - T M Bespalova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article presents the results of the research of expressiveness of the content-meaning and instrumental-style characteristics, analyses the correlations between the variables of the structure of military college students' responsibility.